The Specificity of the Text of Synthetic Nature in the Sociocultural Space of the 20th Century - Osmukhina, Olga Yurievna; Kuryaev, Ilgam Ryasimovich; Startsev, Dmitry Ivanovich (Journal of History Culture and Art Research, 2019)
The article considers suppositions and implementation of "figurativeness" of literature in the modern cultural context. The intersection in the process of the synthesis of arts generates polyartistic domain within the framework of a unified author’s text. The phenomenon of this process has started to be examined only since the beginning of the 19th century, but examples of synthetic art can be found since Antiquity. The tendency to synthesis is inherent both in some art forms and a number of separate genres. The synthesis of different types of arts can be carried out within a particular work or at the intersection of two or more works belonging to different types of art. The very understanding of the "synthesis of arts" has undergone changes in its assimilation, but the basic principle of creating a new form remained constant. At the same time, in the" watershed" periods, the actualization of synthesis was observed, which contributed to the emergence of new artistic objects. At the same time, literature was influenced greatly and, first of all, by cinema. By the example of Boris Akunin’s novels, it is possible to observe how, following the author’s strategy, the novel space is filled with cinematic and illustrative imagery, which contributes to the creation of polyartistic, polysemantic in the figurative and expressive respect of the text.